Optimal scheduling model of hydro-photovoltaic complementary based on simulation optimization algorithm - Dacheng Li; Xianfeng Huang; Xu Li; Di Wu; Jian Zhou (Energy Reports, 2023)
The total amount of hydro-photovoltaic generation is limited by the grid channel after large-scale grid connection of photovoltaic in the hydro-photovoltaic complementary clean energy base, resulting in the reduction of power generation efficiency of the system, an optimization scheduling model of hydro-photovoltaic complementary with yearly, monthly and daily scheduling cycles is established. The model adopts the simulation optimization algorithm, introduces the photovoltaic absorption measurement method, aiming at maximizing the power generation benefit of the system, and finally determines the cascade hydropower dispatching method. Taking the Tibet section of the Mekong River as an example, five typical hydrological years are cited to conduct a case study on the optimal scheduling of the hydro-photovoltaic complementary clean energy base. The results show that, on the basis of guaranteeing the hydropower benefit, this dispatching method can effectively improve the photovoltaic absorption rate, and realize the improvement of the total power generation benefit of the hydro-photovoltaic complementary base.